The effect of transformation policies on healthcare providers' satisfaction in primary healthcare centers: the case of Eastern Saudi Arabia - Arwa Abdulrahman Althumairi; Fatmah Muhammad Bukhari; Layan Bassam Awary; Duaa Aljabri (BMC, 2023)
Abstract Background The Saudi Arabian Vision 2030 encompasses the Health Sector Transformation Program (HSTP), an initiative aimed at enhancing the accessibility, affordability, and quality of healthcare, with a strong emphasis on patient-centered care. To achieve this vision, the government has been providing training to Primary Healthcare (PHC) centers on patient-centered care, recognizing that spending quality time with patients is crucial for making informed clinical decisions. Therefore, it is essential to evaluate provider satisfaction with the quality of services they provide and assess the impact of organizational factors on care quality. This study represents the first comprehensive assessment of job satisfaction among PHC providers in the Eastern region of Saudi Arabia. It seeks to gauge job satisfaction among PHC providers and explore its associated impact on the quality of care they deliver. Methods This study employed a quantitative cross-sectional design. Data were collected using a modified version of the Job Satisfaction Survey (JSS), supplemented by three newly added dimensions. Additionally, questions addressing general characteristics were incorporated into the survey instrument. Data analysis involved calculating frequencies and percentages for univariate analysis, employing t-tests for comparisons between two groups, and utilizing ANOVA for comparisons among multiple groups (bivariate analysis). Results A total of 143 PHC providers took part in this study. Of these, 48% reported high satisfaction, while the rest were either dissatisfied or neutral. PHC providers were highly satisfied with supervision (17%, N=94). On the other hand, they were dissatisfied with contingent rewards (3%, N=15). There was a significant difference found between the intention to leave the job (yes, no) and job satisfaction scores (mean (SD)= 83.58 (16.174) vs. mean (SD)=101.64 (16.209), p-value < 0.001). There were also significant relationships between general characteristics and the dimensions such as co-workers, promotion, responsibility, nature of work, operating procedure, and communication (p-value< 0.05). Conclusion The main findings of this study suggest that PHC providers working in PHC centers in the Eastern region were satisfied with their work, especially with supervision and patient care. However, the findings also revealed that there are many areas of the job of PHC providers that require planned reform, such as contingent reward and communication. Furthermore, intention to leave the job was significantly related to job satisfaction score and all the dimensions. The study findings will help policymakers and the Ministry of Health to develop an employee engagement and satisfaction program to track the PHC providers' levels of satisfaction.